Efficacy of first-year GnRHa therapy in girls with idiopathic central precocious puberty diagnosed after age 8: a retrospective study - Ming-ming Ni; Shu-ting Yang; Jie-yu Sun; Wen-wen Wu; Man Li; Wei Gu; Xing Ji (Gynecological Endocrinology)
Purpose This study aimed to evaluate the short-term benefits of GnRHa therapy, with a specific focus on the first year of treatment, in girls diagnosed with idiopathic central precocious puberty (ICPP) after age 8, providing essential evidence to inform clinical decision-making.Methods Ninety-four female patients treated with GnRHa at Jiangsu Children’s Medical Center from January 2018 to January 2021 were retrospectively reviewed. Patients were divided into two groups based on the age of treatment initiation: on or before age 8 (Group I) and over age 8 (Group II). Hormonal parameters, bone age (BA)/chronological age (CA) ratio, genital organ volume, predicted adult height (PAH), and body mass index (BMI) were assessed during the treatment period.Results Treatment with GnRHa in girls with ICPP, whether administered before or after age 8, effectively inhibited puberty, slowed BA maturation, and led to an increase in PAH. Group I exhibited significantly better PAH improvement than Group II, with 50% surpassing a 5 cm increase in PAH compared to 25.9% in Group II. No significant changes in BMI were observed following treatment.Conclusions The findings of the study support the knowledge that GnRHa treatment is effective in height gain in girls with precocious puberty, especially if started before the age of 8 years.